Human capital externalities and growth of high- and low-skilled jobs - Jens Suedekum (Institute for the Study of Labor (IZA), 2006)
In this paper I analyze the impact of human capital on local employment growth for the case of West Germany (1977-2002). I find robust evidence that skilled cities grow faster than unskilled ones, but this need not indicate localized human capital externalities are at work. A large initial share of high-skilled workers significantly reduces subsequent growth of high-skilled jobs. The observed positive impact on total employment growth is, therefore, due to the fact that low-skilled jobs grow faster than high-skilled jobs decline in initially skilled cities. This evidence is in line with complementarities among skill groups as the major causal link between human capital and employment growth. It challenges theories of self-reinforcing spatial concentration of high-skilled workers due to strong localized spillovers.
Keywords: R11; O40; 330; human capital; local employment growth; externalities